Using a Composite Maternal–Infant Outcome Measure in Tuberculosis-Prevention Studies Among Pregnant Women. (4th November 2020) - Montepiedra, Grace; Kim, Soyeon; Weinberg, Adriana; Theron, Gerhard; Sterling, Timothy R; LaCourse, Sylvia M; Bradford, Sarah; Chakhtoura, Nahida; Jean-Philippe, Patrick; Evans, Scott; Gupta, Amita
Abstract: Background: Tuberculosis (TB-)-preventive therapy (TPT) among pregnant women reduces risk of TB in mothers and infants, but timing of initiation should consider potential adverse effects. We propose an analytical approach to evaluate the risk–benefit of interventions. Methods: A novel outcome measure that prioritizes maternal and infant events was developed with a 2-stage Delphi survey, where a panel of stakeholders assigned scores from 0 (best) to 100 (worst) based on perceived desirability. Using data from TB APPRISE, a trial among pregnant women living with human immunodeficiency virus (WLWH) that randomized the timing of initiation of isoniazid, antepartum versus postpartum, was evaluated. Results: The composite outcome scoring/ranking system categorized mother–infant paired outcomes into 8 groups assigned identical median scores by stakeholders. Maternal/infant TB and nonsevere adverse pregnancy outcomes were assigned similar scores. Mean (SD) composite outcome scores were 43.7 (33.0) and 41.2 (33.7) in the antepartum and postpartum TPT initiation arms, respectively. However, a modifying effect of baseline antiretroviral regimen was detected ( P  = .049). When women received nevirapine, composite scores were higher (worse outcomes) in the antepartum versus postpartum arms (adjusted difference, 14.3; 95% confidence interval [CI], 2.4–26.2; P  = .02), whereas when women received efavirenz there was no difference by timing of TPT (adjusted difference, .62; 95% CI, −3.2–6.2; P  = .53). Conclusions: For TPT, when used by otherwise healthy persons, preventing adverse events is paramount from the perspective of stakeholders. Among pregnant WLWH in high-TB-burden regions, it is important to consider the antepartum antiretroviral regimen taken when deciding when to initiate TPT. Clinical Trials Registration. NCT01494038 (IMPAACT P1078). Abstract : Prioritization of events in a composite outcome reflects stakeholder beliefs about risk–benefit trade-offs in mothers and infants. For women on nevirapine-containing regimens, deferring tuberculosis-prevention therapy to the postpartum period is better for the overall well-being of the mother–infant pair.